Serial changes in coronary plaque formation using CT angiography in patients undergoing PCSK0-inhibitor therapy with 1-year follow-up - Baumann, Stefan; Kettel, Laura; Stach-Jablonski, Ksenija; Özdemir, Gökce Havva; Renker, Matthias; Tesche, Christian; Becher, Tobias; Hetjens, Svetlana; Schoepf, U. J.; Akın, Ibrahim; Borggrefe, Martin; Krämer, Bernhard; et al. (Journal of thoracic imaging, 2022)
Purpose: Previous studies have shown positive effects of intensive low-density lipoprotein (LDL)-lowering therapy on atheroma volume using invasive intravascular ultrasound. This study describes the changes in coronary plaque composition on coronary computed tomography angiography in patients treated with proprotein convertase subtilisin kexin type 9 (PCSK9) inhibitors. - Materials and Methods: In this prospective study, coronary plaques were analyzed using third-generation dual-source computed tomography before and after 1 year of PCSK9-inhibitor treatment. Plaque markers included total plaque volume (TPV), calcified plaque volume (CPV), noncalcified plaque volume (NCPV), lumen volume and vessel volume (VV), minimal luminal area (MLA), minimal lumen diameter (MLD), corrected coronary opacification, eccentricity, remodeling index, and functional plaque parameters. Primary endpoint was defined as change in TPV; the secondary endpoint was TPV or CPV regression or nominal change in plaque parameters. - Results: We analyzed 74 coronary plaques in 23 patients (60±9 y, 65% male). After 1 year of PCSK9-inhibitor treatment, LDL was reduced from 148 to 66 mg/dL (P<0.0001). Significant changes were found for VV (196 to 215 mm3, P=0.0340), MLA (3.1 to 2.6 mm2, P=0.0413), and MLD (1.7 to 1.4 mm, P=0.0048). TPV, CPV, NCPV, lumen volume, and functional plaque parameters did not change significantly (P>0.05). - Conclusions: Coronary artery plaque analysis by coronary computed tomography angiography highlights that LDL lowering therapy affects plaque composition. The primary endpoint of TPV change was not reached; however, VV, MLA, and MLD changed significantly.
Gesehen am 13.02.2023